Prevalence and Associated Factors of Depression in Women in the Last Trimester of Pregnancy: A Cross-Sectional Study in a Southern Province of Vietnam - Huỳnh, Khai Quang; Dong, Le Minh Quan; Tran, Tai Nang; Nguyen, Quach Giang My; Truong, Thanh Nam; Duong, Phuc Lam; Le, Thi Gai (Scripta Medica, 2026)
Background/Aim: Depression during pregnancy is a significant public health issue, particularly in the third trimester when women experience various physical and emotional changes. This study aimed to investigate the prevalence of depression and anxiety among women in the final trimester of pregnancy, as well as the associated factors.Methods: A cross-sectional descriptive study was conducted involving pregnant women in their last three months of pregnancy who attended regular prenatal check-ups at the prenatal clinic of Phuong Chau International Hospital in Can Tho. The Edinburgh Postnatal Depression Scale (EPDS) was used to screen for depressive symptoms.Results: The present study found a prevalence of depression of 14.3 %. Symptoms of depression were significantly associated with a history of previous miscarriage (p = 0.004), a history of abortion (p < 0.001), treatment for vulvovaginitis (p = 0.002) and satisfaction with the marital relationship (p = 0.003).Conclusion: This study identified factors associated with depressive symptoms in pregnant women during their third trimester. Absence of previous miscarriage, absence of abortion history, no treatment for vulvovaginitis and marital satisfaction were associated with lower odds of depressive symptoms.